2013
DOI: 10.1002/2013wr013722
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modeling of flow tomography experiments in fractured media

Abstract: [1] The accurate characterization of the location, hydraulic properties, and connectivity of major fracture zones is essential to model flow and solute transport in fractured media. Cross-borehole flowmeter tests, which consist of measuring changes in vertical borehole flows when pumping a neighboring borehole, were shown to be an efficient technique to provide information on the properties of the flow zones that connect borehole pairs. The interpretation of such experiments may, however, be quite uncertain wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Recently, Hochstetler et al (2016) used HT to investigate a highly heterogeneous (K range of 10 −7 to 10 −1 m/s) unconsolidated sedimentary aquifer at HRFS with highquality results. For HT in fractured aquifers, synthetic and field studies using drawdown, tracer, and temperature data have been conducted in 2D (e.g., Hao et al 2008;Klepikova et al 2014;Trottier et al 2014;Wang et al 2016;Somogyvári et al 2017;Fischer et al 2018), and 3D (e.g., Klepikova et al 2013) but we are only aware of distributed-parameter 3D HT field studies at the Mizunami research site in Japan (Illman et al 2009;Zha et al 2015). The Mizunami studies were at the scale of >0.5 km lateral and vertical extent, or considerably larger than the HRFS focus of this paper and in situ remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hochstetler et al (2016) used HT to investigate a highly heterogeneous (K range of 10 −7 to 10 −1 m/s) unconsolidated sedimentary aquifer at HRFS with highquality results. For HT in fractured aquifers, synthetic and field studies using drawdown, tracer, and temperature data have been conducted in 2D (e.g., Hao et al 2008;Klepikova et al 2014;Trottier et al 2014;Wang et al 2016;Somogyvári et al 2017;Fischer et al 2018), and 3D (e.g., Klepikova et al 2013) but we are only aware of distributed-parameter 3D HT field studies at the Mizunami research site in Japan (Illman et al 2009;Zha et al 2015). The Mizunami studies were at the scale of >0.5 km lateral and vertical extent, or considerably larger than the HRFS focus of this paper and in situ remediation.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was first proposed by Londe and Sabarly [] and has been extensively employed to examine the pressure‐sensitive permeability of fractured rocks [ Cornet and Morin , ; Cornet et al ., ; Cappa et al ., ; Derode et al ., ]. In a complete HPPT, however, the flow in the tested rocks is particularly prone to become non‐Darcy as a result of high flow velocities and hydraulic gradients in the cracks or fractures [ Derode et al ., ; Klepikova et al ., ], and the interpretation of the experimental data becomes quite difficult because the flow path geometry is in nature complex and full of uncertainties, even being altered under high fluid pressures due to hydraulic fracturing [ Doe and Geier , ]. Hydraulic fracturing is an effective stimulation technique for oil and gas production in low‐permeability reservoirs [ Yang et al ., ; Adachi et al ., ; Gu and Mohanty , ], but this process should generally be avoided in hydraulic engineering for reducing the risks of cracking, tensile failure, permeability enhancement, and leakage in rocks [ Fehler et al ., ; Rubin , ; Jiang et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Zha et al (2014), through synthetic simulations, found that the joint inversion of steady-state head and flux data induced by pumping can lead to a better characterization of hydraulic properties in a synthetic fractured medium. Generally, flux or flow rate data are more sensitive to fracture connectivity, and thus can provide complementary information about fracture properties with respect to traditional head data (Klepikova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%